PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN FLIPBOOK DALAM PEMBELAJARAN MEMBACA PEMAHAMAN TEKS CERITA PADA PESERTA DIDIK KELAS V SDN KARANGROTO 02 SEMARANG - Ristra Putri Ariesta; Rida Fironika Kusumadewi; Yunita Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the application of the flipbook-assisted Problem Based Learning (PBL) model in learning to read and comprehend story texts in grade V students of SDN Karangroto 02 Semarang. The method used is quantitative research with a pseudo-experimental design. The results of the study showed that the application of the flipbook-assisted PBL model can improve students' reading comprehension of story texts. Students showed a significant improvement in reading comprehension ability after using this model. Therefore, the flipbook-assisted PBL model can be used as an effective learning alternative in improving the understanding of story texts in elementary school students. The application of the flipbook-assisted problem-based learning model in learning to read and comprehend story texts. This is evidenced by the student score of reaching the KKTP as many as 31 complete students with an average score of student learning outcomes. The research data showed that the score of the application of the flipbook-assisted problem-based learning model in learning to read and comprehend the story text. before receiving treatment, namely with an average score of 77, consisting of 15% completed and 85% incomplete. And student learning outcomes after receiving treatment using the application of the flipbook-assisted problem-based learning model in learning to read and comprehend story texts with an average of 88 consisting of a percentage of students who completed 100%, and students who did not complete 0%.